Kolegia karno-administracyjne w walce z Kościołem katolickim w Polsce (1956-1970) - Marcin Łysko (Czasopismo Prawno-Historyczne)
In the years 1956-1970 the relations between the state and the Church were increasingly tense, especially since the latter tried to win more influence in the society. In response, the state authorities intended to reduce the position of the Church through a number of administrative measures, which included i.a. refusals to allow religious meetings and gatherings for religious celebrations, or raising funds for religious purposes. In those actions, local authorities were supported by administrative penal courts whose main task was to repress the clergy and lay Catholics who had infringed the existing laws. Matters related to the activities of the Church were dealt with by specially appointed judiciary boards and documented in separate reporting files. The main penalty was pecuniary in the form of a fine, usually adjudicated in the highest amount in case of clergymen, and in lower values in case of lay offenders. The most frequent violations of the existing laws that were subject to prosecution and punishment included illegal gatherings and illegal public fund rising for religious purposes. Alongside a fine, a forfeiture of the raised sum was also common. Those repressions and penalties had, for some time, limited the activity of Polish clergy and had a negative impact on the assets of the Church, which had nevertheless came out victorious from that confrontation with communist authorities.